Strategy To Improve The Operation And Maintenance Performance Of Irrigation Networks For Water-Using Farmers (P3A) In The Pekan Dolok Irrigation Area, Sub-District. Dolok Masihul, District, Serdang Bedagai - Wardi, Eko Pramasto; T Sabrina; Nuradi, T Erry (SEAN Institute, 2024)
Field problems that occur in the Operation and Maintenance of irrigation networks are obstacles for the Water-Using Farmer groups and the relevant Government in improving the effectiveness of irrigation Operation and Maintenance performance which need to be followed up immediately. This research is quantitative research with a SWOT analysis approach. Using the total sampling method with a total of 85 respondents consisting of all members of the Water User Farmers. The research results were proven to have proven validity and reliability with rtable = 0.1796. Analyzed using SWOT (Strength, Weakness, Opportunity, Threat). The results of the SWOT matrix conclude that the performance of Water User Farmers has not been effective in the Operation and Maintenance of Irrigation Networks, as well as conclusions regarding 4 strategies to maximize its effectiveness, namely: (1) Involve all members of Water User Farmers without exception in all activities held by the User Farmer group. Water and programs held by related agencies such as construction and maintenance of irrigation network facilities. (2) Involve local communities around the Irrigation Network Operation and Maintenance area in the construction of irrigation network facilities so that they also feel they can benefit from the government program. Use craftsmen from them and not use craftsmen from other areas. (3) Form a security team consisting of members of the Water Using Farmers group without exception to resolve the problem of unilateral water monopoly by several individuals. (4) Hold regular events involving the parties involved, namely members of Water-Using Farmers, local communities and related agencies so that good communication patterns and a sense of belonging between each other are established.